It takes two to tango: The interactive effect of authentic leadership and organizational identification on employee silence intentions. (August 2016) - Monzani, Lucas; Braun, Stephan; van Dick, Rolf
Organizational silence is a state of affairs in which employees refrain from voicing problematic issues at work. It often results from the dilemma between considering the short-term interests of the leader, who might perceive voicing problems as disloyal, and the long-term interests of the organization, which might suffer severe costs because of silence. In this article we propose a theoretical model that bridges authentic leadership and organizational identification to test their joint effect on organizational silence responses (exit, loyalty and neglect). Based on previous work, we hypothesized that authentic leadership is positively related to employees' loyalty (a passive yet constructive response). However, in dilemmatic situations this effect should be buffered by a high organizational identification (as a result of conflicting loyalties). Similarly, in such situations, we predicted that the influence of authentic leadership on employees' destructive responses may be counter-productive if not matched with a high organizational identification. We tested our proposed model with an online vignette study that involved 458 employees from German-speaking countries from diverse work sectors. We used a realistic scenario comprising a dilemmatic situation, in which a decision between voice and silence had to be made. Our results partially support the hypotheses. Implications for management and future research directions are discussed.